2004
DOI: 10.1007/s00775-004-0524-5
|View full text |Cite
|
Sign up to set email alerts
|

Carbamoylphosphonate-based matrix metalloproteinase inhibitor metal complexes: solution studies and stability constants. Towards a zinc-selective binding group

Abstract: Overactive matrix metalloproteinases (MMPs) are associated with a variety of disease states. Therefore, their inhibition is a highly desirable goal. Yet, more than a decade of worldwide activity has not produced even one clinically useful inhibitor. Because of the crucial role of zinc in the activity of the enzyme, the design of inhibitors is usually based upon a so-called zinc binding group (ZBG). Yet, many of the hitherto synthesized potent inhibitors failed clinically, presumably because they bind stronger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 25 publications
0
49
0
Order By: Relevance
“…CPCPA was synthesized as previously described (20). It is a stable, white, water-soluble, crystalline solid with a melting point of 163jC to 164jC, pK a1 < 2, pK a2 = 5.35 (19).…”
Section: In Vitro Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…CPCPA was synthesized as previously described (20). It is a stable, white, water-soluble, crystalline solid with a melting point of 163jC to 164jC, pK a1 < 2, pK a2 = 5.35 (19).…”
Section: In Vitro Assaysmentioning
confidence: 99%
“…Our group is involved in a study directed toward this goal. We found that the carbamoylphosphonic function is capable of complexing zinc ions with some selectivity (19) and we recently reported the first examples of the novel class of carbamoylphosphonates synthesized and studied as potential MMPIs (20). A group of alkylcarbamoylphosphonate and cycloalkylcarbamoylphosphonate compounds are described in our recent publication (20).…”
mentioning
confidence: 99%
“…MMPs aid tumor progression by increasing cancer cell growth, migration and invasion, angiogenesis and metastasis 26,27 . In recent years, we have reported in a series of papers that show CPOs are able to act both in vitro and in vivo as inhibitors of the extracellular MMP 2 [16][17][18] and possess zinc-binding ability 28 . The three enzyme families (ATX, CA IX and XII and MMP 2) have significant differences in their substrates and their products, but share similarities in the fact that they all have zinc ions at their catalytic sites and furthermore, they function in the extracellular medium.…”
Section: Discussionmentioning
confidence: 99%
“…Among α-functional phosphonic acids, carbamoylphosphonates are important class of compounds that exhibit a variety of interesting and useful properties. Recently, carbamoylphosphonates have been reported as a new zinc-binding group for selective matrix metalloproteinases (MMP) inhibitors [6,7]. In contrast to the widely studied α-functional phosphonic acid derivatives [8][9][10][11][12], relatively few papers have reported on the chemistry of carbamoylphosphonates, although there is evidence that carbamoylphosphonates are pharmaceutically active [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%